Phonon Characterization, Structural and Optical Properties of Type-II CdSe/CdTe core/shell and Type-II/type-I CdSe/CdTe/ZnS core/shell/shell Quantum Dots - Xuan Ca, Nguyen; Thi Hien, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 36 No 3, 2020)
The CdSe, type-II CdSe/CdTe core/shell and type-II/type-I CdSe/CdTe/ZnS core/shell/shell  quantum dots (QDs) were successfully synthesized in a noncoordinating solvent. The phonon characterizations, optical properties and structures of the synthesized QDs were characterized by Raman scattering (RS) spectra, photoluminescence (PL) spectroscopy, PL-decay lifetime, absorption spectroscopy (Abs), and X-ray diffraction (XRD). The growth of QDs was monitored by using RS, which demonstrated the formation of correct of the core/shell and core/shell/shell structures. Observation results from XRD reveal that all QDs crystallize in the cubic phase with zinc-blende structure. The typical characteristics of spatially indirect recombination for type-II QDs were observed through Abs and PL spectroscopy. The ZnS shell significantly enhanced the PL quantum yeild (QY), the optical durability, the chemical stability and separating CdSe/CdTe QDs from the surroundings. The effect of excitation power on the PL properties of the CdSe core,  CdSe/CdTe and CdSe/CdTe/ZnS QDs has been investigated.